Determinants of Banks’ Profitability Before and During The Financial Crisis: Evidence from UK - Ou, Haibo (2011)
This dissertation seeks to investigate the bank-specific and macroeconomic factors that determine the profitability of a sample of 73 banks in the United Kingdom for the period of 2003-2010. To evaluate the impact of the recent financial crisis, the testing period splits into the pre-crisis period, 2003-2006, and the during-crisis period of 2007-2010. The results derived from the Fixed-Effect panel data method indicate banks with a higher cost efficiency and larger size generally have lower profitability. Both credit risk and capitalization are negatively related to the bank profitability while a healthy liquidity generates a positive effect to bank performance. With regard to macroeconomic variables, only economic growth exhibits a significant and positive relationship with bank profitability. According to the results, the late 2007 financial crisis exerts a negative and significant impact on the profitability of UK banks but a more ambiguous and inconsistent picture emerged in the determinants of cost efficiency, bank size and capital strength between pre- and during-crisis periods. Although the signs of liquidity, credit risk and economic growth are constant in all testing periods, none of them generates a significant effect to ROAA from 2003 to 2006. The importance of internal and macroeconomic factors extends this study to further implications on cost management and risk management practices in current situations.